1996
DOI: 10.1016/0014-5793(96)01056-3
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D is involved in cytosolic phospholipase A2‐dependent selective release of arachidonic acid by fMLP‐stimulated rat neutrophils

Abstract: The production of phosphatidic acid (PA) from phosphoAbstract When rat polymorphonuclear neutrophils (PMN) were treated with N-formyI-Met-Leu-Phe (fMLP), the release lipase D (PLD)-catalyzed hydrolysis of phosphatidylcholine is of araehidonie acid in preference to other fatty acids was a rapid and widespread response of cells stimulated with diobserved. Levels of arachidonic acid reached a plateau within verse agonists, and is implicated in a broad spectrum of 5 rain, and were accompanied by an ,-~ 4-fold incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…The introduction of a combination of PA and DAG reconstituted full cPLA 2 activity in permeabilized human PMN cells, while addition of either PA or DAG alone evoked only partial activation of cPLA 2 , suggesting that PLD acts as an upstream regulator in the induction of PLA 2 activity. Fujita et al showed that treatment of neutrophils with ethanol (PA acceptor) or propranolol (PA phosphohydrolase inhibitor) suppressed the FMLP-stimulated AA release, and they suggested that cPLA 2 may be downstream of the PLD-dependent signaling pathway in FMLP-stimulated neutrophils (45). In this study we demonstrated that the inhibition of PA production via a transphosphatidylation reaction in the presence of a primary alcohol does not affect the WKYMVm-induced cPLA 2 activation (Fig.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The introduction of a combination of PA and DAG reconstituted full cPLA 2 activity in permeabilized human PMN cells, while addition of either PA or DAG alone evoked only partial activation of cPLA 2 , suggesting that PLD acts as an upstream regulator in the induction of PLA 2 activity. Fujita et al showed that treatment of neutrophils with ethanol (PA acceptor) or propranolol (PA phosphohydrolase inhibitor) suppressed the FMLP-stimulated AA release, and they suggested that cPLA 2 may be downstream of the PLD-dependent signaling pathway in FMLP-stimulated neutrophils (45). In this study we demonstrated that the inhibition of PA production via a transphosphatidylation reaction in the presence of a primary alcohol does not affect the WKYMVm-induced cPLA 2 activation (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…(44). Treatment of neutrophils with ethanol, an inhibitor of PA formation by PLD, suppressed FMLP-stimulated AA release, suggesting that PLD acts upstream of PLA 2 in neutrophils (45). However, the interrelationship between PLA 2 and PLD in the context of superoxide generation has not been studied extensively in human monocytes.…”
Section: The Wkymvm-induced Stimulation Of Cpla 2 and Pld 1 Is Requirmentioning
confidence: 99%
“…Several lines of evidence have suggested a functional correlation between PLA 2 and PLD enzymes during cell activation [24–30]. We [24] and others [25–27] have reported that stimulus‐induced AA release, which appears to be mediated by cPLA 2 , is suppressed by pharmacological inhibition of PLD. Moreover, PLD 2 , not PLD 1 , activity has been reported to be modulated by cPLA 2 or its reaction products [28–30].…”
Section: Introductionmentioning
confidence: 87%
“…Butanol Attenuated Increased Protein Levels of cPLA 2 and Cox-2 But Not PLD2 in Snca -/-Microglia Because cPLA2 and subsequent arachidonic acid metabolism by enzymes like Cox-2 have been demonstrated to be downstream of PLD activity in immune cells [38,39] it was possible that changes in PLD activity might be autoregulating PLD2 expression and feed-forward regulating the increases in cPLA 2 or Cox-2 protein levels. To assess whether the changes in protein levels were due to PLD activity, PLD-mediated generation of phosphatidic acid was attenuated by treating cells with increasing concentrations of butanol [40,41].…”
Section: Snca -/-Microglia Displayed Increased Protein Levels Of Selementioning
confidence: 99%